2017
DOI: 10.21608/mjppf.2017.124286
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Behavior of Some Root and Grain Quality Traits Under Water Deficit and Normal Conditions in Rice (Oryza Satival.)

Abstract: This study aimed to determine heterosis, gene action, heritability, genetic advance and phenotypic correlation response to select and predict by the new lines for some root traits (Root length, Root volume, Number of roots/plant and Root/Shoot ratio %) and some grain quality traits. Flush water irrigation was added every 12 days intervals. The results indicated that highly significant and positive heterosis as a deviation from mid-and better-parent were obtained for all root and grain quality, except for grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…In contrast, dominance gene action, additive × dominance and dominance × dominance types of gene interaction showed highly significant values, indicating that these factors are significant contributors to the variation of generation means, which were involved in the inheritance of such characters, similar results were reported by Hassan (2017) and Santosh et al (2014) . Since additive gene effects were non-significant for these characters, a simple selection procedure in the early generations may not contribute significantly to improving these characters.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, dominance gene action, additive × dominance and dominance × dominance types of gene interaction showed highly significant values, indicating that these factors are significant contributors to the variation of generation means, which were involved in the inheritance of such characters, similar results were reported by Hassan (2017) and Santosh et al (2014) . Since additive gene effects were non-significant for these characters, a simple selection procedure in the early generations may not contribute significantly to improving these characters.…”
Section: Discussionsupporting
confidence: 83%
“…Significant positive estimates of heterosis and heterobeltiosis among physiological and agronomic traits and its components in two studied crosses, which revealed the over-dominance plays an important role in inheritance of those traits. These findings were supported by several studies ( Ahmadikhah, 2018 ; Hossain et al, 2021 ; Kamara et al, 2017 ; Tiwari et al, 2019 ), wherein it has also been suggested that these aforementioned crosses could be used to explore the heterotic effects in hybrid rice breeding programs with water deficit conditions ( Concepcion et al, 2015 ; Guimarães, Stone & Silva, 2016 ; Hassan, 2017 ; Hastini et al, 2021 ; Potkile et al, 2018 ). Furthermore, significant heterosis percentages were recorded for these traits in studied crosses, which was corroborated by previous studies ( Gaballah et al, 2021 ; Ouyang, Li & Zhang, 2022 ; Sakran et al, 2022 ).…”
Section: Discussionsupporting
confidence: 53%